Advertisements for children's entertainment products in a popular parenting magazine: sedentary or active? - Corey H. Basch; Aleksandar Kecojevic; Valerie Cadorett; Charles E. Basch (Tabriz University of Medical Sciences, 2017)
Background: The purpose of this study was to describe advertisements of children's entertainment products in a popular magazine, Parents, and to determine if they illustrated behavior that was physically active or sedentary. Methods: The sample was comprised of Parents magazines (January 2010 to December 2015). Coding involved determining if the advertisement was promoting sedentary or active behavior. Results: Nearly all of the 169 advertisements in the sample (n = 166; 97.6%) were for products that depicted sedentary behavior. The most common types of entertainment products advertised were DVDs (n = 72), plastic stacking products (n = 18), books (n=14), and electronic devices (n = 13). The most popular theme that appeared in the advertisements was the entertainment product would enhance intelligence (n = 85; 50.3%, 95% CI: 0.43-0.58). The overwhelming majority (n = 136; 80.5%. 95% CI: 0.76-0.87) of the advertisements involved the presence of a character. Conclusion: This type of advertising does not contribute to the nation's goals of increasing physical activity among youth.